Restoration of tallgrass prairie degraded by the noxious weed sericea lespedeza - Gatson, Garth Arnold (Kansas State University, 2018)
The largest intact remnant of the tallgrass prairie, the Flint Hills ecoregion, is currently under threat from the invasive weed sericea lespedeza (Lespedeza cuneata [Dumont] G. Don; SL). The objectives of this research were to evaluate the efficacy of late-season prescribed burning and fall herbicide application, alone and in concert, for comprehensive control of sericea lespedeza and to assess their broader treatment impacts on native plant communities. A 31-ha native tallgrass pasture with a light to moderate infestation of SL was divided into 16 subunits for this experiment. Each subunit was randomly assigned to 1 of 4 treatments: negative control, spray-only, burn-only, or burn-plus-spray. A prescribed burn was conducted on burn-only and burn-plus-spray subunits in early September 2016. Following the re-emergence of SL, spray-only and burn-plus-spray subunits received a broadcast application of metsulfuron methyl (Escort XP, DuPont, Wilmington, DE) at a rate of 70.1 g ˖ ha⁻¹ in late September. Frequency and vigor of SL, total forage biomass, soil cover, and plant species composition were measured along permanent 100-m transects in each subunit prior to treatment application and again 12 mo later, in 2017 (i.e., 1 YAT). In 30 x 30-cm plots at 1-m intervals along each transect, the presence or absence of SL was noted. Where SL was present, crown maturity and maximum stem length of the SL plant nearest to the transect were recorded. Presence of multiple stems in plots was also recorded. Prior to treatment application, SL comprised 1 ± 2.0% of total basal cover and was not different between treatments (P = 0.38). One YAT, SL was more abundant (P ≤ 0.02) in negative control subunits than in spray-only, burn-only, or burn-plus-spray subunits, which were not different (P ≥ 0.95) from one another. Aerial frequency of SL, abundance of mature SL crowns, and incidence of plots with multiple SL stems were greatest (P ≤ 0.03) for negative controls, although not different (P ≥ 0.50) between the other 3 treatments. The change in forage biomass production 1 YAT did not differ (P = 0.16) between treatments. A tendency (P = 0.06) for a shift from litter cover to bare soil was noted when the spray-only, burn-only, and burn-plus-spray treatments were compared to the negative control. Graminoid basal cover was greater (P < 0.01) in the spray-only and burn-plus-spray treatments than in the negative-control and burn-only treatments 1 YAT. Conversely, forb basal cover was less (P = 0.01) in spray-only and burn-plus-spray treatments than in negative-control and burn-only treatments. The evenness component of diversity decreased in the burn-plus-spray treatment relative to the negative control (P ≤ 0.01). These data indicate that each of these strategies were effective in reducing SL populations. Although late-summer prescribed burning produced no detected negative responses within the native plant community, fall herbicide application, alone or in conjunction with prescribed burning, resulted in collateral damage to forb populations. A late-summer prescribed burn alone is recommended for low-cost comprehensive control of a light to moderate sericea lespedeza infestation.
Keywords: Herbicide; Lespedeza cuneata; Prescribed fire; Tallgrass prairie